Fibrinopeptide A release is necessary for effective B:b interactions in polymerisation of variant fibrinogens with impaired A:a interactions - Soya, Keisuke; Terasawa, Fumiko; Okumura, Nobuo (Thrombosis and Haemostasis, 2013)
Fibrin polymerisation is mediated by interactions between knobs ‘A’ and ‘B’ exposed by thrombin cleavage, and holes ‘a’ and ‘b’. We demonstrated markedly delayed thrombin-catalysed fibrin polymerisation, through B:b interactions alone, of recombinant γD364H-fibrinogen with impaired hole ‘a’. To determine whether recombinant variant fibrinogens with no release of fibrinopeptide A (FpA) polymerise similarly to γD364H-fibrinogen, we examined two variant fibrinogens with substitutions altering knob ‘A’, Aα17A- and Aα17C-fibrinogen. We examined thrombin- or batroxobin-catalysed fibrinopeptide release by HPLC, fibrin clot formation by turbidity and fibrin clot structure by scanning electron microscopy (SEM) and compared the results of the variants with those for γD364H-fibrinogen. Thrombin-catalysed FpA release of Aα17A-fibrinogen was substantially delayed and none observed for Aα17C-fibrinogen; fibrinopeptide B (FpB) release was delayed for all variants. All variant fibrinogens showed substantially impaired thrombin-catalysed polymerisation; for Aα17A-fibrinogen it was delayed less, and for Aα17C more than for γD364H-fibrinogen. No variants polymerised with batroxobin, which exposed only knob ‘A’. The inhibition of variant fibrinogens’ polymerisation was dose-dependent on the concentration of either GPRP or GHRP, and both peptides that block holes ‘b’. SEM showed that the variant clots from Aα17A- and γD364H-fibrinogen had uniform, ordered fibres, thicker than normal, whereas Aα17C-fibrinogen formed less organised clots with shorter, thinner, and tapered ends. These results demonstrate that FpA release per se is necessary for effective B:b interactions during polymerisation of variant fibrinogens with impaired A:a interactions.
Keywords: Fibrin polymerisation; B:b interaction; fibrinopeptide A release; knob ‘A’, hole ‘a’